Trauma in traffic in Montenegro between 2004 and 2010. (1st March 2011) - Pejakovic, M; Utjesinovic, J; Bogdanovic, M; Pavlicic, R; Tadic, N; Knezevic, V; Pejakovic, V
Abstract : The first car showed up in Montenegro in 1902. There are 177 677 cars in Montenegro. Every third citizen owns a car. The total cost of the damage created by road accidents is estimated to 2% of the GDP, which makes the issue of traffic safety one of the issue with priority. The aim of this study is to make the trauma in traffic in Montenegro be seen so that the prevention programmes could be created. Method: Data used was found in police reports in the given period. The data had been analysed, statistically processed and shown in the shape of a graph. Results: 30% of cars is between 10 and 20 years old. About 41 000 cars is between 20 and 30 years old. Only a quarter of cars has the age that is less than 10 years. 12 913 persons were hurt in Montenegro from 2004 to 2010. 9559 (74%) person were slightly injured, 2830 (22%) were seriously injured and there were 524 (4%) of those who were dead. Average number of injured persons in road traffic accidents is 2152 per year. Death rate (deaths/100 000 persons) is 14/100 000 persons from given period. The drivers consist 46% (239) of cases of the total number of those killed. Co-drivers consist about 34% (177) and pedestrians consist about 20% of the cases (108). Conclusion: By identifying the main sources of traffic accidents and applying all activities of prevention we can decrease the consequences of the things mentioned above.